(untitled) (Journal of Contemporary Studies, 2014)
Abstract Since the end of cold war the balance of power has dominantly shifted to the pax Americana making the United States of America the leading hagemon in world politics. The onset of war on terror since 2001 and consequent US global policies in pursuit of Bush doctrine of pre-emption have created a global power imbalance. China being part of an energy-rich Caspian Region and in proximity of the oil-rich Persian Gulf has emerged as the largest economy of the world. In order to sustain its global economic stature China needs to secure its trade beyond Asia by securing the sea lines of communications in Indian Ocean. In order to counter balance Chinese influence in Indian Ocean, the USA has adopted a New Defence Strategy. It has made major strategic restructuring in Indian Ocean first time since 1945. It has plans to shift 60 per cent of its naval vessels to South Pacific by 2020. This paper is an analysis of the implications of the US strategy in Indian Ocean for Chinese strategic designs.